A VOF-based 3D numerical investigation of evaporating, deformed droplets. (23rd July 2009) - Schlottke, J.; Dulger, E.; Weigand, B.
We present 3D numerical simulations of evaporating, deformed droplets using an in-house DNS Code which solves the incompressible Navier Stokes equations and employs the Volume of Fluid (VOF) method in order to account for multiple phases. The vapour phase is represented by an additional VOF variable and the evaporation rate is computed based on the mass fraction gradient at the interface (Schlottke and Weigand, 2008). The potential of the method is demonstrated for different cases of evaporating droplets. A distinct relationship between the droplets' shape and the mass transfer intensity is found as part of the results.